Предмет: Алгебра,
автор: nikaremer
решите уравнение способом введения новой переменной:
(x^2+x+1)(x^2+x+2)-6=0
Ответы
Автор ответа:
4
пусть x²+x+1=t, тогда:
t*(t+1)-6=0
t²+t-6=0
D= 1+24= 25
t1= (-1+5)/2= 2
t2= (-1-5)/2= -3
1) x²+x+1=2
x²+x-1=0
D= 1+4= 5
x1= (-1+√5)/2
x2= (-1-√5)/2
2) x²+x+1=-3
x²+x+4=0
D<0 корней нет
Ответ: x1= (-1+√5)/2, x2= (-1-√5)/2
Похожие вопросы
Предмет: Математика,
автор: kate8279
Предмет: Алгебра,
автор: akameambidekstr
Предмет: Химия,
автор: liliabogdanova1617
Предмет: Физика,
автор: ddianakushnir
Предмет: История,
автор: bffgfggfgot75